The Influence of Length of Rehabilitation Process for Ex-Nickel Mining Land on Soil pH, Soil Organic Matter, Population and Distribution of Soil Microbes - Timur Priono; Retno Rosariastuti; Sudadi Sudadi; Mujiyo Mujiyo; Widyatmani Sih Dewi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This study aimed to analyze the influence of rehabilitation length process of the ex nickel mining land on soil pH, SOM, population and soil microbial distribution in East Halmahera, North Maluku, Indonesia. Purposive sampling method was taken under completely randomized design (CRD) with variation of rehabilitation length process: 0, 2, 4, 6, and 8 years. The parameter included soil pH, SOM, population and soil functional bacteria. Data was analyzed using ANOVA and continued by Duncan Multiple Range Test (DMRT) at 5% error level. The result showed the length of rehabilitation process can reduce soil pH, increasing bacteria and fungi population. Four years of rehabilitation process in 2020-Nancy with special treatment of intensive watering resulted the best soil quality characterized by soil pH 6.48, SOM 4.03%, bacteria population of 85 × 10¹ CFU/g, fungi population of 7 × 10¹ CFU/g, non-symbiotic nitrogen-fixing bacteria of 7.0 × 10¹ CFU/g, phosphate-solubilizing bacteria of 0.5 × 10¹ CFU/g, potassium-solubilizing bacteria of 1.0 × 10¹ CFU/g, and proteolytic bacteria of 3.0 × 10¹ CFU/g. The rehabilitation length of 4 years with intensive watering is recommended to provide nutrient and soil microbial on ex-nickel mining rehabilitation. Keywords: Bacteria, Fungi, Nickel, pH, SOM.